Assembling Neoliberalism : Expertise, Practices, Subjects - Higgins, Vaughan; Larner, Wendy (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
This book examines how neoliberalism is constituted from multiple, diverse elements; how these elements are brought together and made to cohere; and the challenges, contestations, and consequences of such. Informed by assemblage thinking, the collection builds on research that emphasizes the forms of experimentation, adaptation, and mutation through which neoliberalism is enacted and rendered workable across different spaces. Contributors provide original case studies on topics such as democratic administration, carbon markets, the sharing economy, behavioral economics, disease management, free trade and youth volunteering. They interrogate the forms of expertise through which neoliberalism is rendered knowable; the diverse socio-technical practices that make neoliberalism governable; and the practices, effects, and tensions involved in the assembling of neoliberal subjects.
Keywords: Social sciences.; Cultural studies.; Social sciences -- Philosophy.; Political sociology.; elektronické knihy; electronic books